Health Quality Assessment of Patients with Toxic-Diffuse Goiter - Saydiganikhodja I. Ismailov1, Komila Kh. Khayitboeva2, Rashid Yu. Ruzibaev3, Duschan Sh. Sapaev4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In recent decades, there has been a significant increase in the number of patients with thyroid disorders[1,4].The widespread introduction of highly informative diagnostics method (ultrasound, fine-needle aspirationbiopsy, tests on hormones and levels of antibody) and screening studies into medical practice led to anincrease in detection rate of thyroid disorders[4,5,8]. Among patients with thyroid pathology, the thyrotoxicosissyndrome significantly complicates the course of thyroid disorders, which makes it difficult to choose arational treatment strategy, affects the long-term result of treatment, and significantly worsens the diseaseprognosis[8,10].